Pengaruh Pupuk Organik Cair Ri1 Terhadap Pertumbuhan Dan Produksi Tanaman Kubis Bunga (Brassica oleracea var. botrytis L.) - L. Gomies; Herman Rehatta; Jean Jean Nendissa (Faculty of Agriculture, Pattimura University, 2012)
Research on the effects of RI1 liquid organic fertilizer on the growth and yield of broccoli (Brassica oleracea L. var. botrytis) has been conducted in Negri Hatalai, Subdistrict of Leitimur Selatan, Ambon. This study was done from January to April 2011. The objective of this study was to obtain optimal concentration of RI1 liquid organic fertilizer for growth and flower yield of broccoli. This research used Randomized Block Design with one factor, consisting of six treatments and three replications. Concentration of RI1 liquid organic fertilizer treatments consisted of 0 ml/0.5 l or without organic fertilizer, 1 ml/0.5 l., 2 ml/0.5 l., 3 ml/0.5 l., 4 ml/0.5 l and 5 ml/0.5 l. The observation data were analyzed using Analysis of Variance and followed by Tukey HSD at a level of 5%. The results showed that the liquid organic fertilizer RI1 did not give significant effects on plant height, stem diameter, time of flower formation, time of flowers opening, flower diameter and weight, but gave significant effects only on leaf number and leaf area at a concentration of 2 ml/0.5 l.